2015
DOI: 10.1111/jorc.12127
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported Medication Adherence in Patients With End‐stage Kidney Disease Undergoing Online‐haemodiafiltration

Abstract: Non-adherence to therapeutic regimens in patients with ESKD is associated with higher levels of triglycerides and higher blood pressure and are, therefore, at a higher cardiovascular risk. Moreover, we found that age and depression status are important variables in non-adherence to therapeutic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
2
8
1
Order By: Relevance
“…21 This study showed that 15.7% of the patients considered themselves as non-adherent to medication. This prevalence is slightly higher than that found in a previous study by our group, 22 in which a prevalence of self-reported non-adherence to medicines was found in 10.7% of the patients, using the Morisky-Green-Levine Measure Treatment Adherence (MTA) scale. In this previous study, a negative association between MTA score and blood pressure and triglyceride serum levels was found.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…21 This study showed that 15.7% of the patients considered themselves as non-adherent to medication. This prevalence is slightly higher than that found in a previous study by our group, 22 in which a prevalence of self-reported non-adherence to medicines was found in 10.7% of the patients, using the Morisky-Green-Levine Measure Treatment Adherence (MTA) scale. In this previous study, a negative association between MTA score and blood pressure and triglyceride serum levels was found.…”
Section: Discussioncontrasting
confidence: 68%
“…The overall adherence score is obtained by summing the responses of questions number 14, 17, 18, 26, 31, and 46, higher punctuation indicated better adherence behavior. Furthermore, questions 11,12,22,23,32,33,41, and 42 measure patients' knowledge and perceptions about treatment. 18…”
Section: Methodsmentioning
confidence: 99%
“…Multiple chronic diseases and polypharmacy, the coprescription of several drugs, are highly prevalent in older persons. 16 18 There is evidence that nonadherence increases with the number of chronic diseases and drugs. The management of chronic diseases required a continuous psychological adaptation and behavioral reorganization that may lead to significant changes with respect to therapeutic indications.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of health management in CKD patients generates high levels of triglycerides and high blood pressure, which increases the risk of developing cardiovascular diseases (Amado et al, 2015; Luis et al, 2016). Life habits are modifiable elements, and these habits must be emphasized to achieve effective health management.…”
Section: Introductionmentioning
confidence: 99%